PENINGKATAN MINAT BELAJAR IPAS MELALUI CULTURALLY RESPONSIVE TEACHING PADA PESERTA DIDIK KELAS IV SDN 01 SUMBERSARI - Dita Hardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine whether the application of culturally responsive teaching can increase students' interest in learning science at SDN 1 Sumbersari, Jember Regency. And how can the application of culturally responsive teaching improve science learning achievement in grade IV students? Based on this research, it can be concluded that: 1) The application of a culturally responsive teaching approach can increase students' interest in learning science in class IV SDN 1 Sumbersari. 2) The application of culturally responsive teaching which can improve science learning achievement of grade IV students is by taking steps that are in accordance with culturally responsive teaching.